Welcome to Westonci.ca, where your questions are met with accurate answers from a community of experts and enthusiasts. Join our Q&A platform to get precise answers from experts in diverse fields and enhance your understanding. Get immediate and reliable solutions to your questions from a community of experienced professionals on our platform.

Use the distributive property to simplify the expressions.
-3(4 - 3p)
-3(7 - 6u)
-6(-1 + 2c)
6(-n + 7)
9(5 + 3c)


Sagot :

Step-by-step explanation:

Do the steps that I did on Problem A for each!!!!

A:-3(4-3p)

a=-3, b=4, c=3p

Apply the distributive law:

[tex]-3*4-(-3)*3p[/tex]

Add minus - plus rules:

[tex]-3*4+3*3p[/tex]

Simplify:

=[tex]-12+9p[/tex]

B:-3(7-6u)

a=-3, b=7, c=6u

=-3*7+3*6u

Simplify;

=[tex]-21+18u[/tex]

C:-6(-1+2c)

a=-6, b=-1, c=2c

=-6(-1)+(-6)*2c

=6*1-6*2c

Simplify:

=[tex]6-12c[/tex]

D:6(-n+7)

a=6,b=-n,c=7

=6(-n)+6*7

=-6n+6*7

Simplify:

=--6n+42

E;9(5+3c)

a=9,b=5,c=3c

=9*5+9*3c

Simplify:

=45+27c